2023
DOI: 10.1038/s41421-023-00529-z
|View full text |Cite
|
Sign up to set email alerts
|

CD36+ cancer-associated fibroblasts provide immunosuppressive microenvironment for hepatocellular carcinoma via secretion of macrophage migration inhibitory factor

Abstract: Hepatocellular carcinoma (HCC) is an immunotherapy-resistant malignancy characterized by high cellular heterogeneity. The diversity of cell types and the interplay between tumor and non-tumor cells remain to be clarified. Single cell RNA sequencing of human and mouse HCC tumors revealed heterogeneity of cancer-associated fibroblast (CAF). Cross-species analysis determined the prominent CD36+ CAFs exhibited high-level lipid metabolism and expression of macrophage migration inhibitory factor (MIF). Lineage-traci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(58 citation statements)
references
References 53 publications
2
56
0
Order By: Relevance
“…Fibroblasts in the TME were also known as carcinoma-associated broblasts (CAFs), which were critically associated with tumorgenesis and tumor progression by boosting angiogenesis, cancer cell proliferation, and invasion. Gui-Qi Zhu reported that CD36 + CAFs in the hepatocellular carcinoma showed high level lipid metabolism and secreted macrophage migration inhibitory factor via the lipid peroxidation/p38/CEBPs axis, leading to an immunosuppressive TME and tumor stemness (Zhu et al 2023). Additionally, after reprogramming of lipid metabolism, lipids metabolites secreted by CAFs were proved to promote CRC migration in a CD36 dependent manner (Gong et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Fibroblasts in the TME were also known as carcinoma-associated broblasts (CAFs), which were critically associated with tumorgenesis and tumor progression by boosting angiogenesis, cancer cell proliferation, and invasion. Gui-Qi Zhu reported that CD36 + CAFs in the hepatocellular carcinoma showed high level lipid metabolism and secreted macrophage migration inhibitory factor via the lipid peroxidation/p38/CEBPs axis, leading to an immunosuppressive TME and tumor stemness (Zhu et al 2023). Additionally, after reprogramming of lipid metabolism, lipids metabolites secreted by CAFs were proved to promote CRC migration in a CD36 dependent manner (Gong et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Et.al observed that metastasis-associated macrophages (MAM) upregulate CD36, which fuel macrophage-tumor crosstalk and reshape the TME ( 34 ). In TME of hepatocellular carcinoma (HCC), a subcluster of cancer-associated fibroblast (CAF) expressed CD36 exhibited high-level lipid metabolism and expression of macrophage migration inhibitory factor (MIF), which interacted with HCC and myeloid-derived suppressor cells to provide immunosuppressive microenvironment ( 35 ). However, despite of quantities of molecular biology studies on CD36, it has not been applied with 18 FDG-PET/CT for distinguishing false negatives yet.…”
Section: Discussionmentioning
confidence: 99%
“…Partial single‐cell studies have highlighted the relevance of the CAFs‐dominated immune barrier in HBV‐HCC immunotherapy. CD36 + CAFs (Table 3) transformed from hepatic stellate cells have been reported to exhibit high levels of lipid metabolism and macrophage migration inhibitory factor (MIF) expression, which were associated with immune evasion 86 . Also, it was stated that CAFs could interact with SPP1 + macrophages to form a tumor immune barrier (TIB) to restrain the infiltration of immune cells into the tumor foci 87 .…”
Section: Novel Insights From Single‐cell Sequencing In Hbv‐associated...mentioning
confidence: 99%